Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Disiplin Kerja Di Dinas Kependudukan Dan Pencatatan Sipil Kota Malang - Yayendra Ning Hayu; Muhammad Ridwan Basalamah; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The aim of this research is: (1) to determine the positive influence of leadership style on the work discipline of the Dispendukcapil Malang City. (2) to determine the effect of the work environment on the work discipline of the Dispendukcapil Malang City. (3) to determine the simultaneous influence of leadership style and work environment on the work discipline of the Malang City Dispendukcapil. In this study, a population of 146 was taken as a sample of 60 respondents. Collecting data through distributing questionnaires using google form.Analysis of the data in this study using SPSS version 16.The technique of testing data with instrument testing uses validity tests, reliability tests, and continued classical assumption tests, multiple linear regression analysis, and research hypothesis testing. The results of the analysis show that: (1) There is a positive influence of the Leadership Style variable on work discipline in the Disdukcapil Malang City. (2) There is a positive influence of the work environment variable on work discipline in the Disdukcapil Malang City. (3) There is a simultaneous influence of leadership style and work environment on work discipline at Disdukcapil Malang City. Keywords: Leadership Style, Work Environment and Work Discipline